The Glasgow Coma Scale following Acute Stroke and In-hospital Outcome: An Observational Study (Journal of Medicine, 2009)
Acute stroke is a heterogeneous condition and the risk of death can be gauged by various factors. This study sought to evaluate GCS score on admission as a prognostic tool of outcome among stroke patients, by observing the GCS score following acute stroke and in-hospital outcome at a tertiary level hospital in Bangladesh. Stroke is a major health problem in developed countries as well as developing countries like Bangladesh. This observational study was conducted among 122 consecutive patients, fulfilling the WHO stroke defining criteria, from 1st January 2007 to 30th June 2007. Mean age was 59.28 ± 14.89(SD) years and male female ratio was 2.39: 1. Cerebral infarct was 49.13%. Intracerebral hemorrhage and subarachnoid hemorrhage was 31.89% and 18.96% respectively. Overall in-hospital mortality was 15.57% though mortality in patients with cerebral infarcts was nil. Patients presenting with GCS between 3 and 8 caused 12.07% fatality, whereas, none died with GCS score 13-15.Here GCS score showed an inverse relationship with outcome that varied with type of stroke. We can conclude that GCS score on admission might be incorporated as an valuable prognostic parameter in stroke outcome measurement scale. doi:10.3329/jom.v10i3.2009 J Medicine 2009; 10 (Supplement 1): 11-14